Distribution and abundance of scaup using baitfish and sportfish farms in eastern Arkansas. Issue 2 (20th November 2020) - Clements, Stephen A.; Dorr, Brian S.; Davis, J. Brian; Roy, Luke A.; Engle, Carole R.; Hanson‐Dorr, Katie C.; Kelly, Anita M.
Abstract: Arkansas' bait‐ and sportfish facilities are commonly used by various piscivorous bird species, including lesser scaup ( Aythya affinis ) and greater scaup ( A. marila ) that consume substantial quantities of fish. To mediate this predation, farmers implement extensive bird harassment programs that create additional costs to fish loss, thus research investigating the distribution and abundance of scaup is needed to help farmers allocate their bird harassment efforts more efficiently. In winters 2016–2017 and 2017–2018 we conducted 1, 368 pond surveys to investigate pond use by scaup on farms during birds' regular wintering period (i.e., November–March). We used intrinsic and extrinsic pond‐level and farm‐level characteristics as explanatory variables in generalized linear models to reveal characteristics associated with increased scaup use. Inter‐annual differences in scaup use were also considered in each model. Our pond‐level model showed that scaup occurred more frequently on larger golden shiner ( Notemigonus crysoleucas ) and fathead minnow ( Pimephales promelas ) ponds stocked at greater densities, particularly during our second study winter. Our farm‐level model suggested that farms further from major rivers and with an average pond size of approximately eight hectares had the greatest probability of scaup use. Producers can apply findings from our models to implement bird harassment efforts in times and locations where scaup predation is more likely to occur.